A house in Lahore : growing up Jewish in Pakistan : a memoir - Kahan, Hazel (United States: Hazel Selzer Kahan, 2022)
Fleeing Germany in 1933 and then Italy in1937 after Mussolini joined the Berlin-Rome Axis, two 27-year-old Jewish physicians follow the advice of a Vatican monsignor to seek a new future in British India. They settle in Lahore, becoming parents of first a daughter and then her brother, three months old in1940 when the family is arrested by the British as "enemy aliens" and interned for almost six years in British internment camps near Bombay. Following the family's release to Lahore in 1946, the children are educated in Lahore's convents and then boarding schools in Kashmir, India and England. After Partition in 1947, Lahore becomes part of Pakistan. In 1971, a new political regime declares Jews are no longer welcome and the family leaves Lahore forever. This memoir describes the contradictions and dilemmas of growing up Jewish in internment and post-British Raj Muslim Pakistan, shuffling identities while learning the futility of belonging and the negotiable meaning of home. Drawing on extensive boarding school correspondence, the book unflinchingly examines the power of letter writing to bind a scattered family yet its inability to prevent schisms. Her father's death releases in the author a compulsion to discover whether her beloved childhood house still stands. Forty years after leaving "forever", she returns to the town of her birth, unsure whether welcome or rejection await but unprepared for what she finds!
In English.
H.B
Keywords: Jewish families Pakistan Biography; Physicians Pakistan Biography